2022
DOI: 10.1186/s12871-022-01824-0
|View full text |Cite
|
Sign up to set email alerts
|

Lower preoperative serum uric acid level may be a risk factor for postoperative delirium in older patients undergoing hip fracture surgery: a matched retrospective case-control study

Abstract: Background Postoperative delirium (POD) is a common complication after hip fracture surgery that is associated with various short- and long-term outcomes. The mechanism of POD may be associated with the oxidative stress process. Uric acid has been shown to provide a neuroprotective effect in various neurodegenerative diseases through its antioxidant properties. However, it is unclear whether lower preoperative serum uric acid levels are associated with the development of POD after hip fracture … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 39 publications
0
14
1
Order By: Relevance
“… 36 , 37 A recent study verified that low SUA level was associated with the increased risk of POD in older patients with hip fracture surgery. 29 Yet surprisingly, no significant difference in the UA level was observed between two groups in our study, however, our multivariate analysis revealed that the SUA/Cr ratio was an independent risk factor for POD in elderly patients undergoing urinary calculi surgery after adjusting confounding factors. The SUA/Cr ratio, an indicator of renal function-standardized UA, has been verified to be relevant to adverse outcomes in multiple diseases, such as metabolic and cardiovascular diseases (CVD), etc.…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“… 36 , 37 A recent study verified that low SUA level was associated with the increased risk of POD in older patients with hip fracture surgery. 29 Yet surprisingly, no significant difference in the UA level was observed between two groups in our study, however, our multivariate analysis revealed that the SUA/Cr ratio was an independent risk factor for POD in elderly patients undergoing urinary calculi surgery after adjusting confounding factors. The SUA/Cr ratio, an indicator of renal function-standardized UA, has been verified to be relevant to adverse outcomes in multiple diseases, such as metabolic and cardiovascular diseases (CVD), etc.…”
Section: Discussioncontrasting
confidence: 72%
“… 28 Meanwhile, we carefully examined all medical and nursing records to evaluate delirium. Referring to the study by Xu et al, 29 patients were included in the POD group according to the following conditions: (1) if the case noted delirium was diagnosed by a psychiatrist; (2) if the doctor’ advice revealed the use of antipsychotics, specifically olanzapine, haloperidol, and quetiapine; (3) if two or more experienced anesthesiologists agreed on the diagnosis of POD by the review of electronic medical records (delirium was screened regularly by trained nurses two times one day). Supplementary Table 1 shows the abstracted symptoms related to DSM-V criteria.…”
Section: Methodsmentioning
confidence: 99%
“…There is discordant evidence regarding the association of serum UA concentrations with postoperative delirium, with some authors finding low serum UA concentrations to be associated with delirium, while others found the same for high serum UA concentrations. Xu et al found a protective effect of high preoperative UA serum concentrations ( p = 0.040) regarding the development of postoperative delirium [ 46 ]. Liu et al found that a lower serum UA concentration to serum creatinine concentration (SUA/SCr) ratio significantly increases the risk of postoperative delirium ( p < 0.001) [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…A prospective cohort study [81] Delirium and long-term psychopathology following surgery in older adults [82] CAM-ICU DSM-V ICD- Postoperative delirium is an independent factor influencing the length of stay of elderly patients in th intensive care unit and in hospital [83] A processed electroencephalogram-based brain anesthetic resistance index is associated with postoperative delirium in older adults: a dual center study [84] Independent external validation of a preoperative prediction model for delirium after cardiac surgery: a prospective observational cohort study [85] Lower preoperative verbal memory performance is associated with delirium after coronary artery bypass graft surgery: a prospective cohort study [86] Effect of regional vs. general anesthesia on incidence of postoperative delirium in older patients undergoing hip fracture surgery [ Lower preoperative serum uric acid level may be a risk factor for postoperative delirium in older patients undergoing hip fracture surgery: a matched retrospective case-control study [90] Risk factors and effect of postoperative delirium on adverse surgical outcomes in older adults after elective abdominal cancer surgery in Taiwan [91] High ASA physical status and low serum uric acid to creatinine ratio are independent risk factors for postoperative delirium among older adults undergoing urinary calculi surgery [92] W wybranej do analizy literaturze najliczniejszą grupę badaną tworzyło 10 755 (36,6%) chorych po operacjach kardiochirurgicznych, a odsetek występowania majaczenia pooperacyjnego dotyczył 2043 chorych. Pozostałe prace dotyczyły odpowiednio 7812 (26,6%) chorych po operacjach ortopedycznych, 5227 (18%) chorych po operacjach brzusznych, 689 (2,3%) chorych po operacjach torakochirurgicznych, 484 (1,6%) chorych po operacjach naczyniowych, 2678 (9,1%) chorych po operacjach neurochirurgicznych, 1714 (5,8%) chorych po operacjach urologicznych.…”
Section: Tytułmentioning
confidence: 99%